Exports, exchange rate movements and the credit markets imperfections: new evidence from threshold regression analysis - Niaz Ahmad, Mohd Naseem; Wan Ngah, Wan Azman Saini; Masron, Tajul Ariffin (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
Based on an innovative threshold estimation technique, this study investigates whether the effect of exchange rate depreciation on exports is distinct with different channels of credit markets imperfections. The empirical results demonstrate the existence of a threshold effect in the relationship between exchange rate depreciation and exports flows. In particular, the impact of exchange rate depreciation on exports is negatively significant only after a certain threshold level of credit market imperfections has been attained. Until then, the exports effect of exchange rate depreciation seems to be non-existent. This finding suggests that the exchange rate depreciation-exports nexus is contingent on the level of credit market imperfection, thereby corroborating the view that credit market imperfection played an important role in impeding exports performance.